Improving the feeding value of rice straw - Josh Davy; Morgan Doran; Dan Macon; Betsy Karle; Glenn Nader; Roger Ingram; Nadia Swanepoel; Peter Robinson (California Agriculture, 2024)
For rice producers, removing straw from a field after harvest is important because the material is slow to break down and needs to be gone prior to planting the next season. One option is to bale the straw and use it as a forage supplement for cattle. Although rice straw is a low-cost supplement, it’s also low in forage quality and digestibility. Three trials over a four-year period tested methods to improve rice straw forage quality in the field where it was harvested, and then tested the treatments in cattle feeding trials to assess intake by cattle, performance in weight and size gain, and forage quality. The goal was to find an economical method to improve rice straw feeding value that was also practical to implement for both rice farmers and beef cattle producers. Of the treatments tested, treating traditionally baled rice straw with ammonia gas improved crude protein, intake and cattle performance, compared to untreated straw. The treatment achieved the goals of being easily transported, practical to implement, and cost effective.